Well leg compartment syndrome after surgery for ulcerative colitis in the lithotomy position: A case report. (2016) - Enomoto, Tsuyoshi; Ohara, Yusuke; Yamamoto, Masayoshi; Oda, Tatsuya; Ohkohchi, Nobuhiro
Highlights: Well leg compartment syndrome is rare complication after surgery in the lithotomy position. Well leg compartment syndrome causes severe neurological and motor dysfunction. Prolonged operative time in the high lithotomy position is the important risk factor for the development of Well leg compartment syndrome. Ileoanal pouch procedure have the high potential for occurring well leg compartment syndrome. Abstract: Introduction: Well leg compartment syndrome (WLCS) is an uncommon and severe complication that occurs after colorectal surgery in the lithotomy position. Presentation of case: The current patient was a 28-year-old male suffering from ulcerative colitis. He was underwent elective proctectomy, including ileal J pouch formation and anal anastomosis with temporary loop ileostomy. The ileoanal pouch procedure was quite difficult, and during this procedure, the high lithotomy and head down tilt positions were continued for 255 min. After the operation, the patient complained of severe cramping pain, swelling and serious tenderness on palpation in both legs. On the first postoperative day, the patient's complaints gradually worsened. The intra-compartmental pressure was measured, and WLCS was diagnosed. Emergency bilateral fasciotomy was performed. Initially, the patient had a sensory deficit and analgesia, however, his sensory disturbance and pain had almost recovered two months after fasciotomy by rehabilitation. Discussion: In the current case, the important factors associated with the development of WLCS are thought to be a prolonged operative time in which the patient is placed in the high lithotomy position during ileoanal pouch procedure. Conclusion: We would thus like to emphasize that operations for the ileoanal pouch procedure to treat ulcerative colitis have a high potential for inducing WLCS, because it usually requires a prolonged operative time in which the patient remains in the high lithotomy position.